Women Journalist in the Middle of Taliban Power - M. Yoserizal Saragih (Budapest International Research and Critics University, 2021)
This article reviews women journalists in the midst of Taliban rule which is being highly discussed in various worlds today. The purpose of this paper is to increase knowledge about what is happening at this time. This paper is a descriptive analysis that aims to describe, inventory, and analyze the conditions being investigated in a systematic, factual and accurate manner, then from the results of the analysis a conclusion can be drawn. The results of the discussion show that after the Taliban succeeded in taking power on August 15, 2021Taliban will respect women's rights, but these rights must be within the limits of Islamic sharia law, women can study and work, women can join the government, Urqa is no longer required as well as women's rights are fulfilled. However, behind the Taliban's power, female journalists in Afghanistan have their own challenges because their rights as women in that country are limited. Since the transfer of power, women journalists in Afghanistan have been threatened, as has been reported in various media.